Teaching Philosophy In Algeria From Traditional To Competency-Based Approaches - Abdelghani ALIOUA & Mohamed TAHIR (Akofena)
Abstract: This article discusses the evolution of teaching philosophy in Algeria, as moving from traditional approaches focused on teaching through indoctrination, to the skills-based approach aims to develop critical thinking and analytical skills amonglearners. The article also highlights some challenges that prevent the improvement of philosophy teaching in secondary education, such as the lack of educational resources and effective tools to implement the teaching of process in a relevant and successful manner; it highlights the importance of reforming curricula and training teachers in modern methods to stimulate philosophical thinking among learners. This work highlights the key stages of philosophy teaching in Algeria and presents the main challengesthat must be overcome to improve the teaching/learning process of philosophy, in accordance with the expectations of the authorities regarding the upbringing of a responsible citizen. The competency-based approach has been adopted as one of the effective methods in training in general, and specifically in teaching philosophy as a subject that is mainly based on dialogue, discussion, and critique, with the aim of building the learner's personality and improving his learning skills. Keywords: traditional approaches, skills-based approach, criticism, learning, didactics.